Elevating Student Motivation: Constructing a Gamified Massive Open Online Courses using the MARC Framework - Saputro, Rujianto Eko; Salam, Sazilah (Universitas Pendidikan Ganesha, 2024)
Education is undergoing a profound revolution in the current era of digital technology, primarily due to the implementation of Massive Open Online Courses (MOOCs). These courses have facilitated worldwide accessibility to education of exceptional quality, transcending geographical and institutional limitations. This study aims to evaluates the implementation of gamification in Massive Open Online Courses (MOOCs) to enhance students' intrinsic motivation and graduation rates. Facing the challenge of low graduation rates in MOOCs, this study designed and implemented a Gamified MOOC (GMOOC) platform using a new gamification framework, MARC. Through an experimental method, this study involved 101 students and collected data through a questionnaire based on the Instructional Materials Motivation Survey (IMMS) and ARCS Model. The data was analyzed using Structural Equation Modelling (SEM), and the results showed that all MARC variables have high reliability and positively impact students' intrinsic motivation, with the Autonomy variable having the most significant impact. This study underlines the importance of a gamification framework in enhancing motivation and graduation rates in MOOCs, as well as the importance of considering the correct design elements and gamification components in the development of MOOCs. This study provides significant implications for developing and implementing effective and engaging MOOCs.